Iatrogenic Critical Care Procedure Complication Boot Camp: A Simulation‐based Pilot Study. Issue 2 (19th February 2019) - Riefkohl‐Ortiz, Elaine; Frey, Jennifer A.; Yee, Jennifer; David Gothard, M.; Hughes, Patrick G.; Ballas, Derek A.; Ahmed, Rami A.
Abstract: Background: Traditional medical education strategies teach learners how to correctly perform procedures while neglecting to provide formal training on iatrogenic error management. Error management training (EMT) requires active exploration as well as explicit encouragement for learners to make and learn from errors during training. Simulation provides an excellent methodology to execute a curriculum on iatrogenic procedural complication management. We hypothesize that a standardized simulation‐based EMT curriculum will improve learner's confidence, cognitive knowledge, and performance in iatrogenic injury management. Methods: This was a pilot, prospective, observational study performed in a simulation center using a curriculum developed to educate resident physicians on iatrogenic procedural complication management. Pre‐ and postintervention assessments included confidence surveys, cognitive questionnaires, and critical action checklists for six simulated procedure complications. Assessment data were analyzed using medians and interquartile ranges (IQRs), and the paired change scores were tested for median equality to zero via Wilcoxon signed rank tests with p < 0.05 considered statistically significant. Results: Eighteen residents participated in the study curriculum. The median (IQR) confidence increased significantly by a summed score of 12.5 (8.75–17.25; p < 0.001). Similarly, the median (IQR) knowledge significantly increased by 6 (3–8) points from the pre‐ to postintervention assessment (p < 0.001). For each of the simulation cases, the number of critical actions performed increased significantly (p < 0.001 to p = 0.002). Conclusion: We demonstrated significant improvement in the confidence, clinical knowledge, and performance of critical actions after the completion of this curriculum. This pilot study provides evidence that a structured EMT curriculum is an effective method to teach management of iatrogenic injuries.